Level of Exposure Elementary School Teachers to the Implementation Merdeka Curriculum - Umar Umar; Syarifuddin Syarifuddin; Mei Indra Jayanti; Irwan Irwan; Indrawan Indrawan (Al-Hayat: Journal of Islamic Education, 2024)
This research examines the exposure and adaptation of prospective elementary school teachers in Bima City to the Merdeka Curriculum, focusing on how these teachers receive information about the curriculum, the training they undergo, and their classroom implementation practices, while also identifying factors that support or hinder the successful adoption of this curriculum. The study employed a descriptive survey method with a quantitative approach, using an electronic questionnaire to collect and analyze data from 44 prospective elementary school teachers at Muhammadiyah Bima University, assessing their perceptions and exposure to the Merdeka Curriculum through descriptive statistics and percentage analysis. Survey results indicate that prospective elementary school teachers in Bima have limited understanding of the Merdeka Curriculum, with only a small percentage having high exposure to it. The study highlights that while 51% of students have moderate exposure, a significant number face challenges in implementing the curriculum effectively due to inadequate resources and practical experience. To address these issues, it is crucial for educational institutions to enhance support through training, resources, and practical experiences, ensuring that prospective teachers are well-prepared to implement the Merdeka Curriculum successfully. This study sheds light on the understanding and exposure to the Merdeka Curriculum among prospective teachers in Bima, revealing a significant gap between theoretical knowledge and practical application. It highlights the urgent need for improved institutional support, including targeted training and better resources, to effectively prepare future educators for implementing the curriculum. The findings offer practical recommendations for enhancing teacher preparation and contribute to the broader discussion on curriculum implementation.